Demographic, Psychosocial, and Contextual Factors Associated With Sexual Risk Behaviors Among Young Sexual Minority Women. (November 2013) - Herrick, Amy; Kuhns, Lisa; Kinsky, Suzanne; Johnson, Amy; Garofalo, Rob
Young sexual minority women are at risk for negative sexual health outcomes, including sexually transmitted infections and unintended pregnancies, yet little is known about these risks. We examined factors that may influence sexual risk from a psychosocial and contextual perspective. Analyses were conducted to examine within group relationships between sexual behaviors, negative outcomes, and related factors in a sample of young sexual minority women. Participants ( N = 131) were young (mean = 19.8) and diverse in terms of race/ethnicity (57% non-White). Sex under the influence, having multiple partners, and having unprotected sex were common behaviors, and pregnancy (20%) and sexually transmitted infection (12%) were common outcomes. Risk behaviors were associated with age, alcohol abuse, and older partners. Results support the need for further research to understand how these factors contribute to risk in order to target risk reduction programs for this population.